Cell Structure, Density and Impact Strength of Cellulose Acetate Foamed with Supercritical Carbon Dioxide. Issue 6 (November 2015) - Ding, Yajun; Ying, Sanjiu
This paper investigated the effects of processing conditions on the cell structure, density and impact strength of cellulose acetate (CA) foamed with supercritical carbon dioxide (SC-CO2 ). The scanning electron microscope (SEM) images show that there is the open-cell structure obviously when the foaming temperature exceeds 210°C, and the increasing foaming temperature improves the amount of open cells. The diameters of external cells range from 0.50 μm to 0.85 μm, and the diameters of internal cells are around 0.20 μm. The presence of cosolvents is beneficial to form open-cell structure, which is ascribed to more amount of CO2 dissolved into the CA matrix. Densities of foamed CA are measured with the method of volumetric flask, and the density ranges between 0.69 g·cm -3 and 1.02 g·cm -3, which are lower than that of the original sample (1.27 g·cm -3 ). The density decreases with increasing the saturation temperature, the saturation time or the foaming temperature. And densities with ethanol are much lower than those with acetone. Both of the impact strengths and specific impact strengths of foamed CA, higher than those of the original sample, increase firstly and decrease subsequently with increasing the foaming temperature. The impact strength of CA foaming at 230°C is 1.4 times higher than that of the original sample, and the specific impact strength increases by 84%.